"Aberrant sialylation plays a significant role in oral squamous cell carcinoma progression". (7th January 2020) - Mehta, Kruti A.; Patel, Kinjal A.; Pandya, Shashank J.; Patel, Prabhudas S.
Abstract: Objective: Aberrant glycosylation, mainly sialylation and fucosylation, is recently considered as a major hallmark of cancer. Aberrant sialylation has long been associated with various neoplastic diseases. However, role of aberrant sialylation in oral cancer is still in its infancy. The present study aimed to examine mRNA expressions of α‐2, 3, α‐2, 6 sialyltransferase (ST) families and sialidase in 160 human oral cancer tissues. Methods: mRNA expression of ST3GAL1, ST3GAL2, ST3GAL3, ST3GAL4, ST3GAL6, ST6GAL1, and neuraminidase 3 (NEU3) was analyzed by RT‐qPCR in 80 paired malignant and adjacent normal tissues from oral cancer patients. Results: The results indicated significant ( P  ≤ .05) down‐regulation of various STs (ST3GAL1, ST3GAL2, ST3GAL3, ST3GAL4, ST3GAL6, and ST6GAL1) and sialidases (NEU3) in malignant tissues as compared to adjacent normal tissues. Higher mRNA levels of ST3GAL2 and ST3GAL3 were significantly associated with advanced stage of the disease, lymph node involvement, and perineural invasion, which denote their role in progression and metastasis of oral cancer. Present study also revealed altered sialylation patterns according to anatomical site of the disease and tobacco habit. Conclusion: The study demonstrated significant role of elevated mRNA levels of ST3GAL2 and ST3GAL3 in disease progression and metastasis of oral carcinoma.